GENETIC DIVERSITY AND GENETIC RELATIONSHIP OF SENGON (Falcataria moluccana) REVEALED USING SINGLE NUCLEOTIDE POLYMORPHISM (SNP) MARKERS - Vivi Yuskianti; Susumu Shiraishi (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2017)
Producing seeds in seed orchards that retain a broad genetic diversity is important for the continued development of a species. The aim of this study was to find out the genetic diversity of, and genetic relationships between several populations of sengon (Falcataria moluccana) in the Candiroto seed orchard in Indonesia. Analysis using twelve single nucleotide polymorphism (SNP) markers showed that the total population had a high level of genetic diversity (He = 0.359±0.128); the Wamena population in Papua had the highest level. The close genetic relationship between this and the population from East Java suggested that the latter may have been introduced from Wamena. There was also a close genetic relationship between the populations from Central and West Java and that from Mindanao Island in The Phillipines. The high genetic diversity of sengon in the Candiroto seed orchard provides a good basis for selection and breeding.